(untitled) (Fiep Bulletin - online, 2011)
Adolescence is considered a crucial period for several changes occur in the human body, it is this stage that they can be numerous diseases carried into adulthood, and which sometimes are caused by lack of exercise. Thus, the Indoor Cycling has the potential to be an alternative, to be an innovative, accompanied by musical sequences that increase the motivation of those involved, easy to learn, held on stationary bike, which limits the risk of accidents, in addition to be practiced in rooms heated by favoring the dissipation of heat by the practitioner. The aim of this study was to evaluate the effects of an indoor cycling program for adolescents in public schools. The program lasted three months, with three weekly training sessions lasting 60 minutes. After signing an informed consent from their parents, participated in the experiment 10 volunteers from schools in the public schools of Santos. Tests were performed before, during and at the end of the experiment, such as assessments of body composition (body weight, height, body mass index, sum of skinfolds and body fat percentage) for testing neuromuscular tests were used and aerobic endurance strength of lower limbs and trunk.